Digital Public Relations Analysis: The Use of Influencers in Socializing The Positive Narrative of Free Nutritious Meals on Social Media - Damayanti Masduki; Hermina Manuhuruk; Yuliani Widianingsih; Joice Soraya; Udi Iswandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The evolution of Web 2.0 has transformed government communication from conventional top-down announcements into dynamic, interactive digital spaces. This study aims to analyze the strategic implementation of digital public relations by examining the use of social media influencers to socialize the positive narrative of the